ANTICOAGULANT EFFECTS OF EMINIUM SPICULATUM AQUEOUS LEAF EXTRACT IN RABBITS - M. I. Al-Farwachi and B.A. AL- Badranii (Basrah Journal of Veterinary Research)
The effect of different doses of Eminium spiculatum aqueous leaf extract on coagulation of blood in the rabbits were studied .Animals treated with extract at a dose of 200 , and 400 mg / kg body weight intraperitoneally daily for 7 days produced a significant ( p < 0.05 ) increase in the clotting time , prothrombin time and activated partial thromboplastin time with normal platelet counts when compared with phosphate buffer saline ( untreated ) and heparin ( treated ) control rabbits. The effect of the extract on coagulation of the blood was shown to be dose – dependent . Result of this study suggest that extract shows considerable anticoagulant activity in rabbits and has potential to reduce cardiovascular morbidity and mortality.